Pengaruh Gaya Kepemimpinan Kepala Sekolah dan Motivasi Kerja Terhadap Kinerja Guru di Madrasah Aliyah Yayasan Pendidikan Jaya Penggalian Kabupaten Serdang Bedagai. - Andari, Yuli; Rambe, Masrina; Maryadi (STAI Tebing Tinggi Deli, 2024)
This research is included in quantitative research. Quantitative research is research that uses numbers either directly taken from research results or data processed using statistical analysis. The results of the study indicate that the principal's leadership style has a significant and positive influence on teacher performance at Madrasah Aliyah Yayasan Pendidikan Jaya Penggalian, Serdang Bedagai Regency. The effective contribution of this variable to teacher performance reached 71.9%, with a relative contribution of 88.9%. This shows that effective principal leadership plays a very important role in improving teacher performance. Work motivation has a significant influence, but with a smaller contribution to teacher performance, namely with an effective contribution of 9% and a relative contribution of 11.1%. Although work motivation is important, in the context of this study, its impact on teacher performance is not as great as the influence of the principal's leadership style. Simultaneously, the principal's leadership style and work motivation together explain 80.9% of the variation in teacher performance. This shows that these two variables are very determining factors in improving teacher performance, although with a clear dominance of the principal's leadership style